Analisis Gender dalam Pengelolaan Hutan Kemasyarakatan (HKm) Di Dusun Gubukrubuh, Desa Getas, Kecamatan Playen - , SRI WULANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In forest management will occur interrelations between forests and people. This is manifested in the form of management activities and the involvement of gender roles in forest management. This study aims to determine the interaction of forests rural women to forest resources, the role of women in the organization HKm farmer groups and rural women's participation in community forest management forest. This research was conducted in Gubukrubuh Hamlet, Village Brittle, Playen District Gunungkidul in February to May 2014. Sampling with purposive sampling method. Data was collected on the family intentionally incorporated in KTHKm Wana Lestari II, which in this case is a woman's status as a wife. The data collected in this study included primary and secondary data, which is then analyzed descriptively with kualitatifndanm quantitative analysis. From this study it can be seen that the interaction of women to forest resources in the community forest land management activities include planting of agricultural crops, looking for twigs for firewood use, as well as planting activities and decision forage. Our role in this is very much KTHKm ranging from participation in routine activities to training. Pesanggem participation of women can be seen from some of the activities that take part in decision-making within the family and in KTHKm, program planners, the division of labor within the family, conducting participate in managing the land share, and play an active role in every training.